Hubungan antara Kadar Serum Albumin Awal dengan Lama Rawat Inap dan Status Pulang Pasien Dewasa di Rumah Sakit - Weni Kurdanti; Hamam Hadi; Susetyowati Susetyowati (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2004)
Background: Several community studies have reported a relationship between a low serum albumin level and increased risk of hospital death, nosocomial infection, and length of stay. But this kind of study is still lacking in Indonesia.Objective: To assess the relationship between admission serum albumin levels with length of stay and recovery rate among adult hospitalized patients.Methods: This cohort study was done in 2002. Subjects of this study were adults, inpatient of internal and neurological departments of Dr.Sardjito, Dr. M. Jamil and Sanglah hospitals. Serum albumin level, total lymphocyte count (TLC), and hemoglobin from each subject were collected at the admission. Energy intake of each subject was obtained using visual Comstock method. Information of length of stay and recovery status at discharge was obtained from medical records.Results: On average the length of stay (LOS) in patients with normal serum albumin was 9.8 days. In patients with low serum albumin the LOS was 2 days longer (p<0.05) than that in patient with normal serum albumin. LOS was not significantly different by serum albuminlevels among neurological and cancer patients. Neurological patients with low serum albumin had 10 times greater risk for not recover on discharge than non neurological patients with normal serum albumin.Conclusion: Serum albumin level at admission was associated with LOS and recovery status on discharge.